2014
DOI: 10.1007/s10620-014-3462-2
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Surgical Complications of Inflammatory Bowel Disease in the Elderly: A Systematic Review

Abstract: Elderly patients with IBD are at an increased risk of hospital- and therapy-related complications. We found a paucity of high-quality studies evaluating outcomes in elderly patients with IBD. Further studies of elderly patients with IBD are needed to further evaluate the effect of age on medical and surgical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
0
20
0
1
Order By: Relevance
“…9, 19 However, reports that note a higher rate of complications in older patients who are treated with immunosuppression also note that there is a paucity of high quality data evaluating treatment-related outcomes in older IBD patients. 7-9, 18, 21 A more recent study reported lower rates of non-infectious complications and a similar rate of infectious complications in elderly-onset CD patients compared to young controls. 9 It is also possible that co-morbidities and polypharmacy may limit the use of biological agents in older adults.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…9, 19 However, reports that note a higher rate of complications in older patients who are treated with immunosuppression also note that there is a paucity of high quality data evaluating treatment-related outcomes in older IBD patients. 7-9, 18, 21 A more recent study reported lower rates of non-infectious complications and a similar rate of infectious complications in elderly-onset CD patients compared to young controls. 9 It is also possible that co-morbidities and polypharmacy may limit the use of biological agents in older adults.…”
Section: Discussionmentioning
confidence: 96%
“…We require a thorough understanding of how the disease process differs in older adults in order to best balance co-morbidities, polypharmacy and use of resources in treating older patients with IBD 6 . Prior reports of IBD in older adults have often focused on those who are newly-diagnosed at an older age; less is known about how IBD evolves with age as patients with IBD survive longer 5, 7-11 . There is also a need to understand how IBD differs between those who age with the disease and those who are newly diagnosed at an older age.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data suggests no difference in patient need for surgical resection based upon age at presentation, and no difference in rates of surgery for hospitalized IBD patients [ 57 ]. As such, surgical management of IBD is safe for elderly patients and should be considered in select individuals but not in the absence of serious thought for the risk of fecal incontinence and decline in quality of life.…”
Section: Infl Ammatory Bowel Diseasementioning
confidence: 99%